Predictors and associated outcomes of adherence to treatment in Russian patients undergoing corneal transplantation - Sergey N. Svetozarskiy; Olga P. Abaeva; Sergey.V. Romanov (Russian Open Medical Journal)
Corneal blindness affects approximately 8 million people worldwide. The effectiveness of keratoplasty depends on several factors, including surgical technique, clinical characteristics of the patients, and social factors such as their adherence to treatment. Objective — To analyze nonattendance of doctor’s appointments and associated clinical outcomes in Russian patients who underwent high-risk and low-risk penetrating keratoplasty (PKP). Material and Methods — We conducted a retrospective cohort study to analyze the pre- and postoperative records of patients who underwent PKP. The low-risk group included 28 people with keratoconus (their mean age was 33±3 years), while high-risk group included 54 people with corneal opacity of various etiologies (their mean age was 67±13 years). The study assessed adherence to treatment by examining attendance at postoperative physician visits. Successful corneal transplant engraftment was considered favorable outcome, whereas graft failure or opacification was considered adverse outcome. The duration of observation was 12 months. Results — Patients in the low-risk group were twice as likely to attend postoperative appointments compared with patients in the high-risk group (p=0.0001). Patients over 70 years of age showed lower adherence to treatment (p=0.016), while those with higher education had significantly improved appointment attendance (p=0.017). Moreover, poor adherence increased the odds of adverse PKP outcome at 12 months in high-risk patients (OR=4.31; p=0.045). Conclusion — Failure to attend postoperative appointments in the high-risk group was associated with older patient age and lower education level, and correlated with adverse clinical outcome in Russian patients.